Capacidade de ligação dos espermatozóides de epidídimo de equinos às células da tuba uterina cultivadas in vitro - Carneiro, João Alexandre Matos [UNESP] (2014)
Several biotechnologies are being developed aiming genetic material conservation of stallions with high zootechnical value, as we can highlight the harvest epididymis’s sperm of animals who suffered trauma or illness that makes impossible the semen collection, death or euthanasia. However these sperm cells do not get in touch with seminal plasma, important whereas it has proteins that participate in processes related to the protection and binding of sperm to the sperm reservoir in the oviduct. In this sense, it suggests that there is significant biochemical changes in epididymal sperm, aiming with this review to study the main morphological and functional differences between the sperm from the epididymis and ejaculated